2014
DOI: 10.1109/lpt.2014.2350772
|View full text |Cite
|
Sign up to set email alerts
|

Linewidth Characterization of Integrable Slotted Single-Mode Lasers

Abstract: A single-mode laser platform has been developed with a simple and high-yield fabrication based on etched slots. We present linewidth measurements on such lasers, which are fabricated without any regrowth steps. The group of slots placed on one side of laser cavity provides sufficient reflectivity for lasing, which allows the laser to be integrated with other devices such as semiconductor optical amplifiers and modulators. The laser with an effective cavity length of 450 µm exhibits a threshold current of 31 mA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 19 publications
0
5
0
1
Order By: Relevance
“…The simulated threshold current under uniform injection is approximately 28 mA compared to experimental measurements of roughly 25 mA. The discrepancy in threshold current can be accounted for in the estimated values for injection efficiency and the spontaneous emission rate [1], [15]. This also compensates for the shift in hopping position of roughly 5-10 mA between experiment and theory.…”
Section: Comparison With Experimentsmentioning
confidence: 79%
See 1 more Smart Citation
“…The simulated threshold current under uniform injection is approximately 28 mA compared to experimental measurements of roughly 25 mA. The discrepancy in threshold current can be accounted for in the estimated values for injection efficiency and the spontaneous emission rate [1], [15]. This also compensates for the shift in hopping position of roughly 5-10 mA between experiment and theory.…”
Section: Comparison With Experimentsmentioning
confidence: 79%
“…Its 37th order grating design had been previously optimized using 24 slots with a depth of 1.35 μm to minimize linewidth while still allowing sufficient transmission of power through the grating [image in Fig. 1(a)] [14], [15]. The 37th order corresponds to a slot width (d s ) of 1.09 μm and period (d p ) of 8.96 μm in order to excite a wavelength of 1550 nm.…”
Section: Introductionmentioning
confidence: 99%
“…In 2014, Abdullaev et al [41] In order to meet the demand of low cost 1550 nm band semiconductor laser chips in the field of optical communication, a coupled-cavity semiconductor laser based on Lot grating structure is proposed by Santa Fe University in Dublin. The single longitudinal mode lasers with SMRR of more than 50 dB are realized in 1569 nm band [43].…”
Section: Coupled Cavity Semiconductor Lasermentioning
confidence: 99%
“…This arises due to the fact that a single FP mode is focussed upon with the grating selection method employed. Abdullaev et al showed that individual FP modes can demonstrate narrower spectral linewidths than conventional DFBs or external cavity diode lasers (ECDL) [13]. Figure 1 shows a scanning electron microscope (SEM) image of the grating.…”
Section: Device Propertiesmentioning
confidence: 99%